Improving Students’ Vocabulary Acquisition and Reading Comprehension by Using the Extensive Reading Approach at Grade 8 of SMP Negeri 2 Silima Punggapungga Dairi - Simanjuntak, Fransisca; Manurung, Lastri Wahyuni (English Education Department at FKIP Nommensen University, 2025)
This study investigates the effectiveness of the Extensive Reading approach in improving vocabulary acquisition and reading comprehension among eighth-grade students at SMP Negeri 2 Silima Punggapungga. Employing Classroom Action Research (CAR), the research was conducted in two cycles, each comprising planning, action, observation, and reflection stages. Data were collected through pretests, posttests, student observations, and teacher reflections. The findings indicate a significant improvement in students' vocabulary acquisition and reading comprehension. The mean vocabulary acquisition score increased from 50.78 in the pretest to 66.09 in Cycle 1 and 79.84 in Cycle 2. Similarly, reading comprehension scores rose from 51.25 in the pretest to 69.53 in Cycle 1 and 80.78 in Cycle 2. The results highlight the positive impact of Extensive Reading, particularly in enhancing students’ motivation, confidence, and independent learning habits. Students became more engaged in reading activities, demonstrated greater autonomy in learning, and exhibited a reduced reliance on translation. Despite these positive outcomes, challenges such as students' varying reading abilities and limited access to reading materials remain. Therefore, providing diverse and engaging reading resources and integrating technology-based reading platforms are recommended to support the sustainability of this approach. This study contributes to the growing body of research on language learning strategies, emphasizing the role of Extensive Reading in fostering literacy skills. Future research should explore its long-term impact and application in different educational settings to validate its effectiveness.